Biederman et al (2019) 2009 vs 2015 comparison - Biederman, Amanda M.; Kuhn, Donald E.; O'Brien, Kristin M.; Crockett, Elizabeth L. (Dryad Digital Repository, 2019)
Polar lipid composition of mitochondrial membranes prepared from cardiac ventricle of Chaenocephalus aceratus and Notothenia coriiceps. Measurements were performed in animals collected in the region of the Western Antarctic Peninsula during the austral fall seasons of 2009 and 2015.